Parenting attitudes and style and its effect on children's school achievements. - Kordi, Abdorreza; Baharudin, Rozumah (Canadian Center of Science and Education, 2010)
The paper reviewed empirical studies on children's school achievements. The contributions of parenting attitude and style were examined in relation to children's school achievement. A strong relationship between children's school achievement and parenting attitude and style was reported in the paper. Findings from the review revealed that authoritative parenting styles were associated with higher levels of children's school achievement, though findings remain inconsistent across cultures and societies. Future studies may explore some of the salient issues underlying the inconsistencies reported in the study, particularly the contradictory results between Asian and European American school children.